Evaluation of Hip Joint Congruence and Range of Motion Before and After Triple Pelvic Osteotomy - McLaughlin, R., Jr.; Miller, C. W. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
Fifteen dogs undergoing triple pelvic osteotomy (TPO) for bilateral hip dysplasia were evaluated prospectively. Ten dogs were treated bilaterally, five dogs were treated unilaterally. Hip joint palpation, radiography and goniometry were performed before surgery and at 5, 10, 15, and 28 weeks after surgery.Joint congruence was significantly improved palpably and radiographically in treated hips while congruence deteriorated in untreated hips. Improvement in congruence was minimal after the five week evaluation. Goniometric measurements were variable but range of motion was generally not decreased after TPO.
Keywords: Triple pelvic osteotomy; joint congruence